Preparation of ZnO and ZnS nanoparticles and in-vitro study of their antimicrobial effect - Mojtaba Falahati; Mostafa Saffari (Islamic Azad University, 2017)
Zinc sulfide (ZnS) & zinc oxide (ZnO) nanoparticles was evaluated for their antimicrobial activity against four pathogenic strains. ZnS&ZnO nanoparticles were synthesized by simple aqueous chemical reaction in an aqueous solution. The main advantage of these nanoparticles (size of 10-30 nm) was that simply could be prepared by using cheap precursors in a cost effective and high throughput manner. Structural, morphological and chemical composition of the prepared nanoparticles were investigated by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and energy dispersion X-ray dispersive fluorescence spectroscopy (EDAX). The antimicrobial effects of the ZnS&ZnOnanoparticls were studied by serial dilution technique and also by well diffusion technique against four pathogenic microorganism strains of Staphyloccusaureus, Escherichia coli, Pseudomonas aeroginosa and Candidiaalbicans. Both nanoparticles of ZnS&ZnO showed antimicrobial activity against both Gram positive Staphyloccusaureus and Gram negative Escherichia coli and Pseudomonas aeroginosa and fungi of Candidiaalbicans. The best antimicrobial efficacy (as MIC of 50 µg/ml) was related to effect of ZnO nanoparticles on Staphyloccusaureus and most resistant pathogen was Candidiaaibicans against ZnS nanoparticles with MIC more than 250 µg/ml. Zinc sulfide (ZnS) & zinc oxide (ZnO) nanoparticles was evaluated for their antimicrobial activity against four pathogenic strains. ZnS&ZnO nanoparticles were synthesized by simple aqueous chemical reaction in an aqueous solution.